A new peirosaurid (Crocodyliformes, Mesoeucrocodylia) from the Upper Cretaceous of Patagonia, Argentina - Barrios, Francisco (2016)
Peirosaurids are a group of Cretaceous continental crocodyliforms from Gondwana. Two species are known from the Neuquén Group in Argentina: Lomasuchus palpebrosus (Portezuelo Formation, late Turonian–early Coniacian) and Gasparinisuchus peirosauroides (Bajo de la Carpa and Anacleto formations, Santonian and early Campanian, respectively). Here, we describe the first peirosaurid from the Cerro Lisandro Formation, Bayomesasuchus hernandezi gen. et sp. nov. The material corresponds to a fragmentary skull and mandible. Although fragmentary, this is the most complete crocodyliform specimen recorded for the Cerro Lisandro Formation. In a phylogenetic analysis Bayomesasuchus is depicted in a polytomy together with South American peirosaurids and the African form Hamadasuchus rebouli.